The Principle and Downhole Testing of Water Injection Exploration in Depleted Reservoirs - Jinpeng Xu; Hui Zhao; Bing Dong; Yi Li; Chuang Wang (Applied Sciences)
Coal mine water hazards are one of the five major natural disasters in mines, and water in depleted areas is the most serious form of water hazard causing casualties. The exploration of depleted areas, especially old tunnels, presents significant challenges, and achieving the required borehole density for exploration in depleted areas is difficult in reality. The authors of this paper previously applied for a patent titled “Water Injection Exploration Method for Depleted Areas Based on Stress Seepage Principle”. In order to theoretically analyze the feasibility of the patented results and validate them in practice, we first analyze the stress distribution and seepage phenomena around the goaf theoretically, construct boreholes underground in Renlou Coal Mine, conducting on-site water injection tests for different zones (depleted areas, old tunnels, and general boreholes), and perform transient electromagnetic observations during the water injection tests. A total of 355 sets of water injection flow rate and pressure data were obtained from different zones in three different boreholes; permeability coefficients were calculated based on the measured data, and relevant diagrams were drawn. Through the analysis of water injection test data and theoretical analysis, the following conclusions were drawn: there are disturbances and stress reduction zones around depleted areas (old tunnels), and when the equivalent normal stress induced by water injection pressure is greater than zero, the permeability of fractures will increase significantly. Whether it is a borehole aimed at depleted areas or old tunnels, it shows the characteristic that the closer the distance to the depleted areas (old tunnels) is, the smaller the water injection pressure, and the larger the permeability coefficient. When water is injected into the disturbance and stress reduction zones of the depleted areas (old tunnels), the water injection pressure can decrease from 9–10 MPa to 3–4 MPa, and the permeability coefficient may even increase in quantity value. The phenomena of pressure reduction and increased permeability during water injection are significantly observable, indicating that the water injection exploration method for depleted areas based on the stress seepage principle is feasible and has practical significance.